Analytical review of digital varnishing and foiling technology - Klymenko, T.; Bukhalenkova, А. (ТОВ «Видавництво Ліра-К», 2025)
In this work the features and advantages of the digital varnishing with digital hot foil stamping technology are presented, including performance advantages, economic benefits for businesses, corresponding to modern trends and demands on the market. Prerequisites and reasons for the relevance of this technology in the context of modern printing market are revealed, using the example of equipment present on the Ukrainian market.
Keywords: market; digital varnishing